Transcriptome Analysis Reveals the Profile of Long Non-coding RNAs During Chicken Muscle Development - Liu, Jie; Zhou, Yan; Hu, Xin; Yang, Jingchao; Lei, Qiuxia; Liu, Wei; Han, Haixia; Li, Fuwei; Cao, Dingguo (Frontiers in Physiology, 2021)
The developmental complexity of muscle arises from elaborate gene regulation. Long non-coding RNAs (lncRNAs) play critical roles in muscle development through the regulation of transcription and post-transcriptional gene expression. In chickens, previous studies have focused on the lncRNA profile during the embryonic periods but there are no studies that explore the profile from the embryonic to post-hatching period. Here, we reconstructed 14,793 lncRNA transcripts and identified 2,858 differentially expressed lncRNA transcripts and 4,282 mRNAs from 12-day embryos (E12), 17-day embryos (E17), 1-day post-hatch chicks (D1), 14 day post-hatch chicks (D14), 56-day post-hatch chicks (D56) and 98-day post-hatch chicks (D98), based on our published RNA-seq datasets. We performed co expression analysis for the differentially expressed lncRNAs and mRNAs, using STEM, and identified two profiles with opposite expression trends: profile 4 with a downregulated pattern and profile 21 with an upregulated pattern. The cis and trans-regulatory interactions between the lncRNAs and mRNAs were predicted within each profile. Functional analysis of the lncRNA targets showed that lncRNAs in profile 4 contributed to the cell proliferation process, while lncRNAs in profile 21 were mainly involved in metabolism. Our work highlights the lncRNA profiles involved in the development of chicken breast muscle and provides a foundation for further experiments on the role of lncRNAs in the regulation of muscle development.